Persistent left superior vena cava and its clinical correlation - A cadaveric study - Mittal, Sachendra Kumar; Parashar, Rekha; Singh, Pankaj Kumar; Jadon, Leena (Asian Journal of Medical Sciences, 2021)
Background: Presented is a case of persistent left superior vena cava draining into the right atrium through coronary sinus and finally opens into right atrium. Abnormalities of the vascular system are more commonly seen due to its importance in circulation. Persistent left superior vena cava is rare but important congenital vascular anomaly. It results when the left superior cardinal vein caudal to the innominate vein fails to regress. The venous anomaly of a persistent left superior vena cava (PLSVC) affects 0.3%–0.5% of the general population. Normally the superior vena cava is a single vascular structure formed by the union of right and left brachiocephalic veins which are in turn formed by the union of internal jugular and subclavian veins of corresponding side, draining the head and neck as well as the superior extremity. Aims and Objective: To evaluate the accuracy of persistent left superior vena cava and to find out the opening of PLSVC and formations of both SVC. Materials and Methods: During routine dissection of Thorax, we have opened the thoracic cage and take out the Heart. during that we found separate SVC and then we did the study on this PLSVC in the Department of Anatomy, Jaipur National University Institute for Medical Sciences and Research Centre (JNUIMSRC) Jaipur and National Institute of Medical Sciences and Research (NIMS & R). Results: We found persistent left superior vena cava in two cadavers out of 30 cadavers (6.66%) one was 64-year-old male cadaver and another 72-year-old male cadaver. Both the vena cavae were formed as of brachiocephalic veins of the corresponding side. The persistent left superior vena cava opened into the enlarged coronary sinus that drained into the right atrium between the opening of inferior vena cava and right atrio-ventricular orifice. Conclusion: It has important clinical implications in certain clinical interventions. It may complicate placement of cardiac catheters or pacemaker leads.